Structural or cyclic? Labor markets in recessions - Edward P. Lazear (IZA World of Labor, 2014)
Persistent unemployment after recessions and the policies required to bring it down are the subject of an ongoing debate. One view suggests there are fundamental changes in the labor market that imply a long-term higher rate of unemployment, requiring the implementation of structural policy reforms. The alternative view is that the slow recovery of the economy is due to cyclic reasons coming from lack of demand which prevents unemployment from falling quickly. Knowing whether higher unemployment is caused by structural change in the labor market or whether the problem is cyclic determines how effective policy can be in addressing the problem.
Keywords: J2; J23; J21; J6; J65; J68; 330; unemployment; mismatch; labor supply; unemployment insurance; monetary policy